Materias didáticos impressos para educação a distância: Interfaces com práticas de linguagem - Ivanda Maria Martins Silva; Michele Rodrigues de Albuquerque (Universidade Estadual de Campinas, 2012)
This paper intends to analyze the production of printed instructional materials for Distance Education, it being understood as a form of distance education students and teachers are physically separated, but united virtually through technological and educational resources. Even with the advances in digital technologies, the print media plays an important role in the processes of mediation between teachers and students. In Distance Education, the physical distance between teachers and students can be minimized, considering the language dialogic in the production of printed instructional materials. The paper will present the key features that guide the production of printedinstructional materialson Distance Education. We also discuss concepts such as: a dialog ic practice in the production of printed instructional materials and the design of text as a mediator and interactive distance learning.